Effect of cold water immersion on 100-m sprint performance in well-trained swimmers - Parouty, J.; Haddad, H. A.; Quod, M.; Lepretre, P.-M.; Ahmaidi, S.; Buchheit, M. (European Journal of Applied Physiology, 2010)
The aim of the present study was to examine the effect of cold water immersion (CWI) on sprint swimming performance in simulated competition conditions. Ten well-trained swimmers (5 males, 5 females; 19.0 ± 3.9 years) performed two 100-m swimming sprints (S1 and S2) interspersed with a 30-min passive recovery period, during which athletes were randomly assigned to 5 min of CWI (14°C) or an out-of-water control condition (CON 28°C). During tests, sprint times, heart rate (HR), pre- and post-race parasympathetic activity via HR variability (natural logarithm of the square root of the mean of the sum of the squares of differences between adjacent normal R-R intervals; Ln rMSSD) and blood lactate accumulation ([La]ac) and clearance ([La]cle) were recorded. Rates of perceived recovery (RPR) and exertion (RPE) were evaluated before and after each sprint. CWI was associated with a `likely` decrease in swimming performance [1.8% (90% CI 0.2, 3.5)], as well as `likely` lower peak HR [-1.9% (-3.6, -0.2)]. CWI was also associated with a `likely` smaller decrease in Ln rMSSD after the first sprint [-16.7% (-30.9, -4.1)]. RPR was `likely` better [+27.2% (-3.7, 68.0)] following CWI. `unclear` effects were observed for [La]ac [+24.7% (-13.4, 79.5)], [La]cle [-7.6% (-24.2, 12.7)] or RPE [+2.0% (-12.3, 18.5)]. Following CWI, changes in sprint times were `largely` correlated with changes in peak HR (r = 0.80). Despite a subjective perception of improved recovery following CWI, this recovery intervention resulted in slower swimming times in well-trained athletes swimming in simulated competition conditions.